Intravenous thrombolysis in stroke mimics: results from the SITS International Stroke Thrombolysis Register. (25th March 2019) - Keselman, B.; Cooray, C.; Vanhooren, G.; Bassi, P.; Consoli, D.; Nichelli, P.; Peeters, A.; Sanak, D.; Zini, A.; Wahlgren, N.; Ahmed, N.; Mazya, M. V.
Abstract : Background and purpose: Patients with stroke mimics (SM), i.e. conditions with stroke‐like symptoms, may risk harm if treated with intravenous thrombolysis (IVT). Current guidelines state low risk of intracerebral hemorrhage based on studies comprising a total of <400 SM cases. We aimed to compare safety and outcomes following IVT between patients with acute ischaemic stroke and mimicking conditions. Methods: We included IVT‐treated ischaemic stroke patients in the SITS International Stroke Thrombolysis Register 2003–2017, examined with magnetic resonance imaging 22–36 h after treatment. Outcomes were parenchymal hematoma (PH) after treatment, symptomatic intracerebral hemorrhage (SICH) per Safe Implementation of Thrombolysis in Stroke Monitoring Study (SITS‐MOST), Second European Co‐operative Stroke Study (ECASS II) and National Institutes of Neurological Disorders and Stroke Study (NINDS) criteria, death and modified Rankin Scale score (mRS) at 3 months. Results: Of 10 436 patients, 429 mimics (4.1%) were identified. The most common types were functional (30.8%), migraine (17.5%) and seizure (14.2%). Patients with mimics had fewer cerebrovascular risk factors and lower median National Institutes of Health Stroke Scale score [7 (interquartile range, 5–10) vs. 8 (5–14), P < 0.001]. Among mimics versus stroke patients, PH was seen in 1.2% vs. 5.1% ( P < 0.001), SICH NINDS in 0.5% vs. 3.9% ( P < 0.001), SICH ECASS II in 0.2% vs. 2.1% ( P = 0.007) and SICH SITS‐MOST in 0% vs. 0.5% ( P = 0.28). Modified Rankin Scale score 0–1 at 3 months was present in 84.1% vs. 57.7% ( P < 0.001) and death within 3 months in 2.6% vs. 5.4% ( P = 0.028) of mimics and stroke patients, respectively. Conclusions: This large observational study indicated that PH and SICH following IVT in patients with SM are uncommon.